Inisiasi Pemberdayaan Ibu-ibu Penggerak PKK Taman Pintar “Tunas Bangsa” Manyaran Kecamatan Semarang Barat Bagi Penguatan Wirausaha Dalam Rangka Persiapan Hari Kesatuan Gerak PKK (HKG-PK) - Novita Mariana; Agus Prasetyo Utomo; Saefurrohman Saefurrohman; Dewi Handayani (Universitas Teuku Umar, 2023)
Community empowerment which is a mentoring activity to help the community develop their own abilities where each individual participates in activities in their environment in accordance with the expected goals. The